Multicriteria analysis of policy alternatives for the conservation calden forest in Córdoba, Argentina - Tello, Diego Sebastián (2018)
The objective of this work is to develop a discrete multicriteria model to evaluate different conservation policies of the native caldén forest of the province of Córdoba, Argentina. The application of the PROMETHEE multicriteria method integrates a private cost benefit analysis that describes the policy effects on farms, and a contingent valuation study that describes the valuation of forest ecosystem services by the urban population of that region. The impact of six policy alternatives considering seven sustainability criteria was simulated. Criteria weighting was applied considering theoretical decision makers profiles, and the preferences expressed by workshop participants as well. The results show that the most preferred alternatives are extension programs with and without prohibition of deforestation. The multicriteria decision analysis shows an almost generalized coincidence, both in the simulation of theoretical weightings and those from the workshop, that the reforestation program with prohibition of deforestation is the best performance alternative and deregulation is the one of worst performance. Only when considering a free-market profile, deregulation turns to have the best performance. It is concluded that multicriteria methods facilitate decision making process, assessing policy alternatives by a wide range of criteria and enabling different actors to express their preferences for these criteria.